ANALYSIS OF SOCIALLY RESTRICTED VOCABULARY AND ITS MORPHOLOGICAL CHARACTERISTICS IN ENGLISH AND UZBEK LANGUAGES - Raimova Nafosat Olimovna, (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This study explores the concept of socially restricted vocabulary, focusing on its linguistic characteristics in English and Uzbek. Socially restricted vocabulary includes terms and expressions used predominantly by privileged or specialized groups within a society, influencing linguistic development and social mobility. The research analyzes the structure, formation, and evolution of such vocabulary, particularly in relation to stopword lists and bigram weighting. Additionally, the study highlights the importance of vocabulary in linguistic studies and examines morphological distinctions between English and Uzbek. The findings contribute to the broader understanding of linguistic stratification and the role of specialized vocabulary in different languages.